Effect of Financial Performance and Investment Decision on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Karona Cahya Susena; Mekar Meilisa Amalia; Irwan Moridu; Pandu Adi Cakranegara; Hengky Leon (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to analyze effect of financial performance and investment decision on company value in Manufacturing Companies Listed on the Indonesia Stock Exchange. The type of research used in this research is quantitative research. The sample in this study is Manufacturing Companies listed on the Indonesia Stock Exchange with the observed period from 2018 to 2021. The sample selection method in this study is purposive sampling. Based on the criteria, the research sample was 36 companies, so the observations that were used as samples for this study were 108 observational data. Hypothesis testing in this study uses a partial test. The results show that financial performance has not significant effect on company value in Manufacturing Companies listed on the Indonesia Stock Exchange. Investment decision has significant effect on company value in Manufacturing Companies listed on the Indonesia Stock Exchange.